Hepatic manifestations in systemic lupus erythematosus - González-Regueiro, José A; Cruz-Contreras, Mariana; Merayo-Chalico, Javier; Barrera-Vargas, Ana; Ruiz-Margáin, Astrid; Campos-Murguía, Alejandro; Espin-Nasser, May; Martínez-Benítez, Braulio; Méndez-Cano, Victor H; Macías-Rodríguez, Ricardo U (Lupus, 2020)
Systemic lupus erythematosus (SLE) is a multi-organic autoimmune disease with a wide variety of clinical manifestations. However, hepatic dysfunction is not included in the diagnostic criteria for the disease and has not been recognized properly. The spectrum of hepatic involvement described in these patients ranges from abnormalities in liver function tests (LFTs) to fulminant hepatic failure. Usually, abnormalities in LFTs are only mild and transient, have a hepatocellular pattern and are not related to SLE but rather are mostly drug related. The most frequent finding on liver biopsy is steatosis (non-alcoholic fatty liver disease). Patients do not frequently progress to advanced chronic liver disease, and their outcome is favourable. Those who develop cirrhosis have traditional risk factors, such as other non-SLE-related conditions. In this work, we aim to review hepatic manifestations in patients with SLE, as well as the diagnostic and therapeutic approaches used for different liver diseases in these patients.